Expression of PD-1/PD-L1 and Inflammasome Mediators in Oral Squamous Cell Carcinoma: Correlation with Key Clinical and Pathological Variables - Fraile-Martinez, Oscar; Garcia-Montero, Cielo; Garrido-Gil, María Jesus; Ríos-Espinosa, Laura; Liviu Boaru, Diego; De Leon-Oliva, Diego; De Castro-Martinez, Patricia; Pereda-Cerquella, Claude; Alhaddadin, Majd N. Michael; Barrena-Blázquez, Silvestra; Rios-Parra, Antonio; Lopez-Gonzalez, Laura; et al. (Journal of Medical Science, 2026)
Objective. Oral squamous cell carcinoma (OSCC) is a leading cause of head and neck cancer morbidity and mortality. This study aimed to explore the relationship between immune checkpoint regulation and inflammasome-related pathways in OSCC, focusing on the Programmed cell death protein 1 (PD-1)/ Programmed cell death ligand 1 (PD-L1) axis and components of the NLR family pyrin domain containing 3 (NLRP3 and NLR family apoptosis inhibitory protein (NAIP) inflammasomes in relation to relevant clinical variables. Design. This retrospective observational study included 30 patients with OSCC who underwent surgical resection. Histopathological expression of PD-1, PD-L1, NLRP3, Apoptosis-associated speck-like protein containing a CARD (ASC/PYCARD), caspase-1, Interleukin-1 beta (IL-1β), IL-18, caspase-5, caspase-8, and NAIP was assessed by immunohistochemistry using ordinal scoring. Associations with clinical features were evaluated using non-parametric tests and Spearman correlation analyses. Inter-marker relationships were explored using correlograms and heatmaps, with stratification by tumour grade. Exploratory binary logistic regression models were applied to examine associations between marker expression and selected clinical variables. Results. Marker expression showed significant associations with tumour grade, relapse, vascular invasion, and oral hygiene, whereas age, sex, smoking status, alcohol consumption, and other clinicopathological variables were not significantly related. Higher-grade tumours exhibited stronger and more extensive inter-marker correlations, suggesting coordinated activation of immune and inflammatory pathways. Increased expression of PD-L1, NAIP, NLRP3, caspase-1, caspase-5, and PYCARD was associated with higher tumour grade, while relapse was linked to elevated expression of NAIP, NLRP3, caspase-1, and IL-18. Poor oral hygiene was inversely associated with the expression of multiple immune and inflammasome-related markers, whereas vascular invasion correlated with broadly increased marker expression. Conclusions. These findings indicate that immune checkpoint signalling and inflammasome-related pathways are closely associated with aggressive clinicopathological features in OSCC. The coordinated expression patterns observed support a role for inflammation-driven immune modulation in disease progression. Although exploratory, this study provides a framework for future investigations aimed at validating these pathways as biomarkers or therapeutic targets in larger cohorts.